지하복합발전플랜트 내의 가스 누출 및 확산에 의한 위험성 평가 인자 분석 - 최진욱; Jin Wook Choi; 이용남; Long Nan Li; 박재용; Jae Yong Park; 성건혁; Kun Hyuk Sung; 이성혁; Seong Hyuk Lee; 김대중; Dae Joong Kim (한국분무공학회지, 2015)
Gas leakage and dispersion in the underground LNG power plant can lead to serious fire and explosion accident. In this study, computational fluid dynamics simulation was applied to model the dynamic process of gas leakage and dispersion phe- nomena in a closed space. To analyze the risk assessment factor, such as the flammable volume ratio, transient simulations were carried out for different scenarios. The simulation results visualized the gas distribution with time in the closed space. The flammable volume ratio was introduced for quantitative analysis the fire/explosion probability.